Infrastructure systems for nuclear energy - Hsu, Thomas T. C. (Thomas Tseng Chuang), 1933- (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
'Infrastructure Systems for Nuclear Energy summarizes this progress with an up-to-date reference to guide the future research and design of infrastructure systems for nuclear energy'--
Includes bibliographical references and index.
Keywords: Nuclear power plants -- Earthquake effects; Reinforced concrete construction -- Design and construction; Nuclear power plants -- Design and construction; Nuclear power plants -- Asia -- Case studies; Nuclear facilities -- Earthquake effects; Nuclear facilities -- Design and construction; Earthquake resistant design